Unity and Togetherness as a Polarization Preventer in the Ya Qawiyyu Tradition of Jatinom Klaten - Ngisomudin, Dinda Aulia; Rodiah, Ita (Universitas Islam Negeri Madura, 2024)
A tradition is something that needs to continue and must be maintained. The Ya Qawiyyu tradition, better known as Sebar Apem, is a tradition originating from Jatinom Klaten. The Ya Qawiyyu tradition was pioneered by Kyai Ageng Gribig, carried out along with the rapid development of Islam in the Jatinom area during the time Sultan Agung ruled in Mataram in 1613-1645. With a qualitative descriptive method, the researcher tries to explain the meaning of unity and togetherness presented by the Ya Qawiyyu tradition. The Ya Qawiyyu tradition offers a profound view of unity and togetherness. Unity in religious harmony is published together with this tradition. It is creating wholeness and stability in life. In terms of togetherness in the Ya Qawiyyu tradition, it certainly easily provides a harmonious and peaceful atmosphere. It can also increase mutual understanding, mutual appreciation, and mutual respect. Not far from that, togetherness can also strengthen the sense of solidarity and kinship among Muslim and non-Muslim communities. The meaning of unity and togetherness in this tradition can easily be one of the answers amid polarization that sometimes still occurs. Forms of polarization such as disputes, discrimination, and even marginalization among religious adherents are melted with the meaning of unity and togetherness in the Ya Qawiyyu tradition, which teaches the value of tolerance, mutual respect, and living in harmony in society.